The roles for branch shelters and sheep manure to accelerate the restoration of degraded grasslands in northern China - Liu, Jing; Schneider, Rebecca L.; Morreale, Stephen J.; Wang, Hongmei; Wang, Ruixia; Wang, Fang; Li, Zhigang (Frontiers in Environmental Science, 2023)
New strategies are desperately needed for restoring the millions of hectares of degraded grasslands in arid and semiarid areas of northern China. This study evaluated using different combinations of manure amendments and shrub branch shelters for their impacts on soil moisture, nutrient availability, and plant growth over two growing seasons in a degraded grassland in Ningxia, China. A two-factor experiment was conducted, with three concentrations of 1.2 g·m-2, 442 g·m-2, and 884 g·m-2 native Tan sheep manure as the main plots. Cut Caragana (Caragana intermedia) branches were used to create branch shelters covering 0%, 20%, 40% and 60% of ground area, and these acted as sub-main plots. Soil water storage, soil temperature, manure decomposition, branch decomposition, soil nutrients, and plant growth were monitored for two years. Results indicated that soil water storage was significantly increased, and soil temperature decreased, under the 40% and 60% branch shelters. Decomposition rate of manure and shrub branches also increased with increasing soil water availability associated with the higher branch sheltering effects, although soil carbon and nitrogen concentrations were primarily driven by the decomposing manure. The combination of high levels of shrub branch shelter and manure application significantly enhanced plant production, although the bulk of the biomass was concentrated in one species, Artemisia scoparia. In conclusion, our study successfully demonstrated feasible and inexpensive solution for the restoration of degraded grasslands, which takes advantage of resources associated with overgrazing Tan sheep and Caragana shrub encroachment in arid and semiarid areas.